Thinking about Indigenous Legal Orders - Napoleón, Val (2014)
Rethinking Indigenous legal traditions is fundamentally about rebuilding citizenship. The theory underlying this paper is that it is possible to develop a flexible, overall legal framework that Indigenous peoples might use to express and describe their legal orders and laws, so that they can be applied to present-day problems. This framework must be able to, first, reflect the legal orders and laws of decentralized (i.e., non-state) Indigenous peoples, and second, allow for the diverse way that each society’s culture is reflected in their legal orders and laws. In turn, this framework will allow each society to draw on a deeper understanding of how their own legal traditions might be used to resolve contemporary conflicts, complex social injustices, and human rights violations.The Canadian state is not going away and the past cannot be undone. This means that Indigenous peoples must figure out how to reconcile former decentralized legal orders and law with a centralized state and legal system. Any process of reconciliation must include political deliberation on the part of an informed and involved Indigenous citizenry. We have to answer the question, «Who are we beyond colonialism?»